Participating life insurance products with alternative guarantees: Reconciling policyholders' and insurers' interests - Andreas Reuß; Jochen Ruß; Jochen Wieland (Risks, 2016)
Traditional participating life insurance contracts with year-to-year (cliquet-style) guarantees have come under pressure in the current situation of low interest rates and volatile capital markets, in particular when priced in a market-consistent valuation framework. In addition, such guarantees lead to rather high capital requirements under risk-based solvency frameworks such as Solvency II or the Swiss Solvency Test (SST). Therefore, insurers in several countries have developed new forms of participating products with alternative (typically weaker and/or lower) guarantees that are less risky for the insurer. In a previous paper, it has been shown that such alternative product designs can lead to higher capital efficiency, i.e., higher and more stable profits and reduced capital requirements. As a result, the financial risk for the insurer is significantly reduced while the main guarantee features perceived and requested by the policyholder are preserved. Based on these findings, this paper now combines the insurer's and the policyholder's perspective by analyzing product versions that compensate policyholders for the less valuable guarantees. We particularly identify combinations of asset allocation and profit participation rate for the different product designs that lead to an identical expected profit for the insurer (and identical risk-neutral value for the policyholder), but differ with respect to the insurer's risk and solvency capital requirements as well as with respect to the real-world return distribution for the policyholder. We show that alternative products can be designed in a way that the insurer's expected profitability remains unchanged, the insurer's risk and hence capital requirement is substantially reduced and the policyholder's expected return is increased. This illustrates that such products might be able to reconcile insurers' and policyholders' interests and serve as an alternative to the rather risky cliquet-style products.
Keywords: 330; participating life insurance; interest rate guarantees; capital efficiency; asset allocation; profit participation rate; policyholder's expected return; solvency capital requirements; Solvency II; SST; market-consistent valuation